Changes on emitter discharge under different water temperature and pressure - Senyigit, Ulas; Cruz, Raimundo Leite [UNESP]; Rodriguez-Sinobas, Leonor; Souza, Wanderley de Jesus (Wfl Publ, 2012)
The study was conducted at the Research Laboratory of Hydraulic and Irrigation Group in the Rural Engineering Department, Technical University of Madrid (Universidad Politecnica de Madrid), Madrid, Spain. Water temperatures of 20, 30, 40 degrees C and system pressures often encountered in irrigation practices of 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190 and 200 k Pa were applied to determine the effects of different water temperatures and pressures on emitter discharge. Non-pressure compensating in-line emitter which has turbulent flow regime with a long-path (labyrinth), emitter discharge was 4 L h(-1) at system pressure of 100 kPa according to the manufacturer recommended, was used. Emitters were spaced 20 cm along the drip laterals with 16 mm diameter. Discharge equations and coefficients of variation related to temperatures of 20, 30 and 40 degrees C were obtained as q = 0.375H(0.51), q = 0.358H(0.52), q = 0.346H(0.53) and 2.68, 2.09, 3.65, respectively. Discharge of the emitter was affected by different system pressures and increased as potentially (R = 0993-0996). In general. the emitter discharge increased with increasing temperature. However, especially in the common system pressures of 90-120 k Pa, differences of obtained emitter discharges between the different water temperatures were not significant (1%).
Keywords: Emitter; discharge; temperature; pressure